LAW AND TRADITION - Abel, Richard (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
The four of us came to Yale and the Law and Modernization Program by different routes. I’m going to describe my background because it explains how Dave and I complemented each other. Influenced by Russia’s launch of Sputnik in fall of my senior year in high school and the fact that I was good at math and science, I majored in physics at Harvard. By the end of my second year, however, I realized I didn’t want to be a scientist: I wasn’t good enough, and it would be years before I could do original work. In spring 1960 I took David Riesman’s SocSci 136 course: “American Character and Social Structure.” It was transformative. The course addressed some of my most pressing personal concerns; for instance, we read Riesman’s “The Lonely Crowd” and Paul Goodman’s “Growing Up Absurd” (1960)— critiques of 1950s culture and pressures for conformity. Allowed to write on almost any topic for our term paper (the only requirement), I chose “Attitudes towards science and extra-scientific phenomena: an empirical study among Harvard students.” (Looking back, I think I was seeking justifications for abandoning physics.) Riesman was a fellow of Quincy House, where I lived, and often had lunch with students, encouraging us to voice dissatisfactions with our Harvard education. My section man sent me a long, laudatory letter about the paper. (He was William Gamson, then writing about social movements in opposition to fluoridation, prefiguring today’s anti-vaxers.) Even more important, Riesman wrote every student (perhaps a hundred of us) about our papers. His 3.5-page letter to me concluded: “One of the things which is most desirable about your paper is the topic itself, chosen and pursued with great originality.” I was hooked.[1] I have always tried to emulate his eclectic, qualitative approach. (A lawyer with no formal training in sociology, he was Henry Ford II Professor of Social Sciences in the Social Relations Department.) The next year I took Paul Freund’s undergraduate course on legal reasoning and felt immediately drawn to law’s pilpul (despite having no background in Talmudic exegesis). I wrote a term paper for him on group libel—only to discover that Riesman had written a long article on the subject (1942)—which, Freund said disparagingly, was the last good thing he ever wrote. In my fourth year I took Talcott Parsons’s first-year graduate course (presumptuously, since I had disdained undergraduate soc rel courses) and was not enamored his formalistic theorizing, which seemed devoid of content. At the same time, I was becoming politically engaged, inspired by the sit-ins and freedom rides (which began in 1960 and 1961, respectively). Although 1950s apathy still pervaded Harvard (the only “demonstration” was a May 1961 protest against changing diplomas from Latin to English), I became active in Tocsin, which opposed above-ground nuclear testing and advocated for nuclear disarmament (doing research and participating in demonstrations in Boston and Washington). What may have clinched my choice of law over sociology graduate school, however, was Columbia’s offer of a full-tuition scholarship (although it was little more than a thousand dollars at the time) and my failure to get a Woodrow Wilson Fellowship. Riesman had urged me to go to Yale Law School for its alleged social science orientation; but I chose Columbia to be close to my girlfriend. (Yes, reader, I married her[2]—and we’re still happily together 58 years later.)